(3OjhGf GdYHGS Hf GdCMfa Hf GdCShOs - (3GdYHGS Hf GdCMfa Hf GdCShO GdMfaj GdjeGej (B[ (3jeGeI fLO (B] (3, CHh GdaVd,J (B192 (3g` s
(3ChdgG (B:s
(3bGd GdYHGS Hf GdCMfa Hf GdCShO ai GdZRd Ydi bGajI GdCda cJH GdeMH Edi GdMHjH QSGdI hGdYjf efg eG JLa ef GdHcG hGdLSe efg bO CVQ Hg GdHdi hGdbdH efg eG jWGhY ef fgG s
(3BNQgG (B:s
(3hbGd CjVkG (B: (3bO cfJ CTch dghi faSi hdXgQg Edi SYjO Hf YKeGf HJUQjL ef Ohf faSi CbaGd dMHce hCfJe di CSHGH CdaGJjL hbGd CjVkG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B259 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B59s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs